Body composition and motor abilities of basketball players - Mladenovic, K.; Laskovic, M.; Mijalkovic, S.; Živkovic, D.; Bjelakovic, L. (23rd International Scientific Conference "FIS COMMUNICATION 2021", 2021)
Basketball is a popular sport, and the fundament of that popularity is based on pronounced attractiveness, game dynamics, and unpredictability. Often the game itself requires a lot of short sprints and a lot of changes in the movement direction in a small space. In addition to good motor skills, for players to satisfy all the requirements of a modern game, it is necessary to have a particular body composition that can contribute to the game one-on-one. This study aimed to determine the relationes of body composition and certain motor abilities of basketball players. A total of 25 basketball players participated in the research. Agility assessment was carried out by the following tests: T-test, Zig-zag test, and Slalom test. For speed assessment, running speed was measured at 5, 10, and 20 meters. Body height, body mass, Body Mass Index, percentage of muscle tissue, and percentage of adipose tissue were measured (calculated) for the body composition assessment. The Kolmogorov-Smirnov test was conducted to confirm the data's distribution normality. The relationship between body composition and motor abilities was assessed using Pearson's coefficient of correlation. We can conclude from the results obtained, that there is a statistically significant correlation between body composition and motor abilities. Statistically significant negative correlation was achieved between percentage of muscle tissue and following tests: Zig-zag (p=0.008), Slalom test (p=0.000) and running speed tests at 5m (p=0.000) and 10m (p=0.000). The percentage of adipose tissue was positively related to T-test (p=0.007) and Slalom test (p=0.018). A positive correlation was also found between the percentage of adipose tissue and the running speed tests at 5m (p=0.003) and 20m (p=0.005). BMI achieved a statistically significant positive correlation only with the T-test (p=0.006). The percentage of body fat and body mass index adversely affects the results of agility. Consequently, we can improve the player's skills by improving body composition. The results emphasize the importance of muscle development because the percentage of muscle mass improves agility and speed results in basketball players.